A Comparative Study on the Future Developments of Human Rights for Tongzhi in China - Deng, Kai (Université d'Ottawa / University of Ottawa, 2014)
There is an increasing movement recognizing LGBT rights in the international arena. In China, “tongzhi” (a Chinese term for LGBT) still face massive discrimination due mainly to the Chinese government’s repressive indifference policy. This thesis follows Kees Waaldijk’s developmental pattern theory of the recognition of gay rights, starting from decriminalisation, anti-discrimination, and reaching partnership legislation. It examines this theoretic pattern in relation to the development of sexual minority rights in the United Nations (UN), European and Canadian human rights law systems. Although every jurisdiction has its own unique aspects, each basically followed Waaldijk’s pattern. The thesis concludes that the application of privacy, equality and non-discrimination principles have helped sexual minorities to achieve equal rights in a variety of fields. The thesis further examines whether the experiences within these three human rights systems can be adopted in the Chinese context. Since the UN laws are soft laws, they will help influence legal reform for tongzhi rights in China but will not be a decisive factor. With regard to the regional human rights model, unlike Council of Europe and the European Union, the Association of Southeast Asian Nations (ASEAN) is unlikely to push the development of human rights in China due to the lack of a strong tie between China and ASEAN member states. The Canadian experience is inspiring but will not be easily duplicated due to the lack of democratic institutions and the absence of an effective judicial review system and judicial independence in China. It is anticipated that the Waaldijk pattern cannot be reproduced in the Chinese context. China will take a top-down reform route in terms of the tongzhi rights development. The central authorities will likely adjust relevant policies to the tongzhi group once a crisis has generated sufficient social pressure that would influence the central authorities to consider changing their repressive indifference policy. Same-sex marriage law is anticipated to be the first tongzhi human right legislation in China due to the Chinese traditional culture of tolerance, the support found among academics, and the current political environment.
Keywords: tongzhi; LGBT; Sexual minority; equality; human rights law; same-sex marriage; China